The problems of typologies of religious personalities (Journal of Philosophy Culture and Political Science, 2018)
The article discusses the concept of «religious person», the substructureof personality religious rights (religious consciousness and religious behaviorand religious relations), analyzes the reasons for the classification types of believers, these foreign and domestic authors. The article has been extensively reviewed by various authors definition of the concept of religious identity and their typological characteristics, the theoretical analysis is performed. The types of religious identity and the reasons for the classification of identified one assesses criteria. The basis of any typology of the system – to show the existence of common characteristics and features between the people and identify their differences. The main purpose of the typology are the regulation of the methodological study of the object and increase its practical significance. Separation of persons in a certain typology for researchers performing the role of assessment tool. In this article, we can say that comparative analysis and classification methods of foreign and Russian authors have been applied to typologies of religious people. The value of the work is to classify them into specific types, taking into account the similarity and personality of people who determine the attitude to religion, which is the common value of people of each type. For our research on this issue, our work can be used as an additional orientation, that is, to identify or classify the types of religious persons and apply them to specific actions, which means that this analysis will increase the practical importance of the work.Key words: religious personality, religiosity, religious consciousness, religious behavior, religious attitude, belief.